The impact of UEFA Euro 2020 football championship on Takotsubo Syndrome: Results of a multicenter national registry - Polimeni, Alberto; Spaccarotella, Carmen; Ielapi, Jessica; Esposito, Giovanni; Ravera, Amelia; Martuscelli, Eugenio; Ciconte, Vincenzo; Menichelli, Maurizio; Varbella, Ferdinando; Imazio, Massimo; Navazio, Alessandro; Sinagra, Gianfranco; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives The UEFA 2020 European Football Championship held in multiple cities across Europe from June 11 to July 11, 2021, was won by Italy, providing an opportunity to examine the relationship between emotional stress and the incidence of acute cardiovascular events (ACE). Methods and results Cardiovascular hospitalizations in the Cardiac Care Units of 49 hospital networks in Italy were assessed by emergency physicians during the UEFA Euro 2020 Football Championship. We compared the events that occurred during matches involving Italy with events that occurred during the remaining days of the championship as the control period. ACE was assessed in 1,235 patients. ACE during the UEFA Euro 2020 Football Championship semifinal and final, the most stressful matches ended with penalties and victory of the Italian team, were assessed. A significant increase in the incidence of Takotsubo Syndrome (TTS) by a factor of 11.41 (1.6–495.1, P < 0.003), as compared with the control period, was demonstrated during the semifinal and final, whereas no differences were found in the incidence of ACS [IRR 0.93(0.74–1.18), P = 0.57]. No differences in the incidence of ACS [IRR 0.98 (0.87–1.11; P = 0.80)] or TTS [IRR 1.66(0.80–3.4), P = 0.14] were found in the entire period including all matches of the UEFA Euro 2020 compared to the control period. Conclusions The data of this national registry demonstrated an association between the semifinal and final of UEFA Euro 2020 and TTS suggesting that it can be triggered by also positive emotions such as the victory in the European Football Championship finals.